2009
DOI: 10.1016/j.lungcan.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Solitary and multiple resected adenocarcinomas after CT screening for lung cancer: Histopathologic features and their prognostic implications

Abstract: Purpose-To study the histopathologic features of CT screen-detected Stage IA adenocarcinomas to determine whether survival differed by the proportion of bronchioloalveolar component (BAC) or by the presence of multiple lesions in node-negative patients.Methods-Five pathologists with expertise in pulmonary pathology examined 279 resected cases of adenocarcinomas, 30 mm or less in length diagnosed by CT screening for lung cancer. The panel determined the consensus diagnosis for each case, identified additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 47 publications
5
121
0
5
Order By: Relevance
“…Multiple studies [1][2][3][4][5][6][7] have shown a 100% 5-year disease-free survival rate, if complete resection is performed for patients with solitary lung adenocarcinoma exhibiting pure lepidic growth (<2-3 cm). Corresponding to adenocarcinoma in situ (AIS) in the International Association for the Study of Lung Cancer/American Thoracic Society/ European Respiratory Society international multidisciplinary classification of lung adenocarcinoma, 8) these tumors are a good indication for sublobar resection.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies [1][2][3][4][5][6][7] have shown a 100% 5-year disease-free survival rate, if complete resection is performed for patients with solitary lung adenocarcinoma exhibiting pure lepidic growth (<2-3 cm). Corresponding to adenocarcinoma in situ (AIS) in the International Association for the Study of Lung Cancer/American Thoracic Society/ European Respiratory Society international multidisciplinary classification of lung adenocarcinoma, 8) these tumors are a good indication for sublobar resection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, among our patient population, 48 patients had a previous history of malignancy, while in 56 patients the pulmonary neoplasm was the only malignancy established. Univariable and multivariable statistical analyses looking at the clinical aspects, such as 36 20 o2 cm e Yoshizawa et al 37 8 Not provided Sakurai et al 38 25 0.5-3.0 cm Yim et al 40 42 is, in our opinion, not a reliable predictor of such, as none of our patients had recurrent disease during the specified follow-up period. We did, however, note a trend towards better prognosis, although not statistically significant, in all those tumors with a lepidic component (P ¼ 0.058).…”
Section: Discussionmentioning
confidence: 70%
“…The authors stated that they had reviewed 11 thousand citations from which they selected 312 that 'met specified eligibility.' The citations supporting their notion, interestingly, have been presented as series of bronchioloalveolar carcinomas or small adenocarcinomas (o2 cm) [29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 5). In some of these, the actual size of the tumor has been at best vague leaving the impression that some of these lesions may not even qualify as adenocarcinoma, but would rather have to be classified as atypical adenomatous hyperplasia (tumors with lepidic growth and size r0.5 cm).…”
Section: Discussionmentioning
confidence: 98%
“…Bu tümörler diğer solid tümörlere göre çok daha uzun "doubling" zamanına sahiptir. Multifokal tümör varlığı, diğer kanser tiplerine göre bu hastalarda sağkalım sürele-rinde daha az etkilidir [18].…”
Section: Bronkioloalveolar Kanserunclassified